The Influence of Digital Communication Competence on Social Interaction Between Students and Lectures - Duki, Duki; Malik, Abdul; Hadi, Tb. Sofwan (Universitas 17 Agustus 1945 Surabaya, 2025)
This study explores the impact of digital communication competence on student–lecturer social interaction in LMS-based digital learning, using the Computer-Mediated Communication (CMC) theory. Employing a mixed-method approach (PLS-SEM and interviews), the study reveals a significant and positive influence of 35.8%. Despite students having strong digital skills, social interaction remains limited due to the LMS’s administrative focus. Qualitative findings emphasize the need for more interactive LMS features that support two-way communication. The study concludes that enhancing digital communication competence and optimizing LMS design within the CMC framework can effectively improve the quality of social interactions in digital learning environments